Is Transitivity Register-specific? A Corpus Exploration of Online Science News - Bonifacio Tala Cunanan (Journal of Language and Literature, 2024)
This paper deals with parsing and exploring transitivity in ten online science news articles in one of the leading national broadsheets in the Philippines. The corpus analysis used two software applications: AntConc and UAM Corpus. Specifically, this study compared the transitivity features of ten online science news with the transitivity features of non-science-based registers. The transitivity analysis of the science-based and the non-science-based registers has resulted in identifying and classifying the underlying semantic roles of Participants, Process types, and Circumstances. Identifying the semantic features across the registers has resulted in identifying the prominent and foregrounded features of transitivity in the corpus. This study reiterates that foregrounding is crucial in stylistic analysis of texts. The analysis has established that while the non-science-based registers use the six Process types, the science-based registers primarily use the Material and the Relational Process types. This disproportionate occurrence of the Process types, especially the non-use of the Behavioral process types, strongly corroborates the notion that transitivity is register-specific. The present study supports a systemic and functional stance that considers language a network of choices applicable across varied genres and registers. Also, this study recommends the use of software applications in language pedagogy. Finally, the findings may also facilitate teaching L2 academic writing and producing science-based materials.